2014
DOI: 10.1073/pnas.1402544111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired functional communication between the L-type calcium channel and mitochondria contributes to metabolic inhibition in the mdx heart

Abstract: Duchenne muscular dystrophy is a fatal X-linked disease characterized by the absence of dystrophin. Approximately 20% of boys will die of dilated cardiomyopathy that is associated with cytoskeletal protein disarray, contractile dysfunction, and reduced energy production. However, the mechanisms for altered energy metabolism are not yet fully clarified. Calcium influx through the L-type Ca 2+ channel is critical for maintaining cardiac excitation and contraction. The L-type Ca 2+ channel also regulates mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 45 publications
7
88
0
Order By: Relevance
“…; Viola et al . , ). Mouse hearts were excised, cannulated onto a Langendorff apparatus via the aorta and perfused with Krebs–Henseleit buffer containing (m m ): 120 NaCl, 25 NaHCO 3 , 4.8 KCl, 2.2 MgSO 4 , 1.2 NaH 2 PO 4 and 11 glucose (pH adjusted to 7.35 with 95% O 2 – 5% CO 2 at 37°C) for 4 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…; Viola et al . , ). Mouse hearts were excised, cannulated onto a Langendorff apparatus via the aorta and perfused with Krebs–Henseleit buffer containing (m m ): 120 NaCl, 25 NaHCO 3 , 4.8 KCl, 2.2 MgSO 4 , 1.2 NaH 2 PO 4 and 11 glucose (pH adjusted to 7.35 with 95% O 2 – 5% CO 2 at 37°C) for 4 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially, the increased dilation of ttubules on the order of ∼150 nm could lead to structural remodelling of the cellular cytoskeleton, leading to the displacement of LTTC and RyR in cardiac junctions on the order of 10-20 nm required to disrupt Ca 2+ release. Consistent with this proposal, the MDX mouse that has no dystrophin has disrupted cellular cytoskeleton (Viola et al 2014) and disrupted calcium release (Cheng et al 2012). In addition, the vinculin-talin-integrin system could likely have a role in t-tubule remodelling, given its linkage to the actin cytoskeleton (Ziegler et al 2008) and the promiscuity of integrin (depending on the receptor sub-type) to bind to different ECM components, including laminin, fibronectin and collagens, including types I, III, IV and VI (Ross and Borg 2001;Tulla et al 2001), which have all been shown to be within the t-tubules (Kostin et al 1998;Crossman et al 2017).…”
Section: Collagens and Nanoscale T-tubule Remodellingmentioning
confidence: 70%
“…In addition, the protein biglycan can bind to both collagen VI and the DGC (Wiberg et al 2001(Wiberg et al , 2002Rafii et al 2006). Dystrophin connects the sarcolemma to cellular cytoskeleton components, including actin filaments and microtubules (Renley et al 1998;Prins et al 2009), which, in turn, link to the L-type Ca 2+ channel (Viola et al 2014). Furthermore, microtubules have been implicated in trafficking both LTTC and RyR to cardiac junctions (Hong et al 2010;Zhang et al 2014).…”
Section: Collagens and Nanoscale T-tubule Remodellingmentioning
confidence: 99%
“…VDAC1 interacts with endothelial NO synthase (eNOS), with such interaction amplifying eNOS activity in a [Ca 2+ ] i -mediated manner (59). VDAC also interacts with the L-type Ca 2+ channel, and it was suggested that impaired communication between the L-type Ca 2+ channel and mitochondrial VDAC contributes to cardiomyopathy (60). Thus, such interactions of VDAC with proteins associated with Ca 2+ transport or activated by Ca 2+ point to VDAC as functioning not only in [Ca 2+ ] i homeostasis but also in many Ca 2+ -regulated cellular activities.…”
Section: Pathways Mediating Ca2+ Fluxes In the Mitochondriamentioning
confidence: 99%